Spin to charge conversion at room temperature by spin pumping into a new type of topological insulator: Α-Sn films - Rojas-Sánchez, J.-C.; Oyarzún, S.; Fu, Y.; Marty, A.; Vergnaud, C.; Gambarelli, S.; Vila, L.; Jamet, M.; Ohtsubo, Y.; Taleb-Ibrahimi, A.; Le Fèvre, P.; Bertran, F.; et al. (Physical review letters, 2016)
We present results on spin to charge current conversion in experiments of resonant spin pumping into the Dirac cone with helical spin polarization of the elemental topological insulator (TI) α-Sn. By angle-resolved photoelectron spectroscopy (ARPES), we first check that the Dirac cone (DC) at the α-Sn (0 0 1) surface subsists after covering Sn with Ag. Then we show that resonant spin pumping at room temperature from Fe through Ag into α-Sn layers induces a lateral charge current that can be ascribed to the inverse Edelstein effect by the DC states. Our observation of an inverse Edelstein effect length much longer than those generally found for Rashba interfaces demonstrates the potential of TIs for the conversion between spin and charge in spintronic devices. By comparing our results with data on the relaxation time of TI free surface states from time-resolved ARPES, we can anticipate the ultimate potential of the TI for spin to charge conversion and the conditions to reach it.